Ethical Sensitivity, Professional Commitment, Whistleblowing Intention: Power Distance as A Moderating Variable - Suyanto, Suyanto; Putri, Fuadhillah Kirana; Adinda, Alywidya (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
This study aims to examine the effect of ethical sensitivity and professional commitment on whistleblowing intentions by adding power distance as a moderating variable. The population of this study were public accountants at Office of Public Accountant (KAP) in the Special Region of Yogyakarta. Consisting of 13 offices with a total of 77 respondents selected using the convenience sampling method. This research is a study that uses a quantitative approach. This study uses primary data by distributing questionnaires. The regression method is used as a data analysis method which is processed using IBM SPSS 23. The results of the study indicate that ethical sensitivity has a positive effect on whistleblowing intentions. Professional commitment has a positive effect on whistleblowing intentions. Power distance does not weaken the relationship between ethical sensitivity and whistleblowing intentions, and power distance weakens the relationship between professional commitment and whistleblowing intentions.